1999
DOI: 10.1136/fn.80.1.f64
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of extended spectrum beta  lactamase producing Klebsiella pneumoniae in a neonatal unit

Abstract: An outbreak of extended spectrum lactamase producing Klebsiella pneumoniae (ESBLKp) in a neonatal unit was controlled using simple measures. Normally, the control of such infections can be time consuming and expensive. Seven cases of septicaemia resulted in two deaths. ESBLKp isolates were subtyped by pulsed field gel electrophoresis, and four of the five isolates typed were identical. Control of the outbreak was achieved by altered empiric antibiotic treatment for late onset sepsis and prevention of cross inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 31 publications
1
34
0
3
Order By: Relevance
“…The observations reported in our study concerning invasive procedures and other conditions are in accordance with those of several authors, who described similar risk conditions for acquisition of HI and death in NICUs (3)(4)(5)8,13,17) During certain periods in the present study, the NICU was overcrowded and we cannot discount the possible breakdown in the application of aseptic techniques, especially hand washing during manipulation of newborns, which have may facilitated cross-infections. These factors have also been mentioned in reports from other hospital units (4,16,21,26,30).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The observations reported in our study concerning invasive procedures and other conditions are in accordance with those of several authors, who described similar risk conditions for acquisition of HI and death in NICUs (3)(4)(5)8,13,17) During certain periods in the present study, the NICU was overcrowded and we cannot discount the possible breakdown in the application of aseptic techniques, especially hand washing during manipulation of newborns, which have may facilitated cross-infections. These factors have also been mentioned in reports from other hospital units (4,16,21,26,30).…”
Section: Discussionmentioning
confidence: 88%
“…This practice have may exerted selective pressures leading to the emergence of multi-drug resistant strains (8,16,26,30), which in turn may have stimulated the acquisition of genes encoding resistance mechanisms via horizontal transfer mechanisms between bacterial strains within the hospital environment (16,29). It is of particular interest, that in this study a significant number of patients (83.1%) received antimicrobial drugs before positive blood culture presentation (empiric use), due to clinical manifestations suggestive of sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Control of epidemics due to this pathogen may benefit from detailed typing. As also demonstrated here, PFGE is effective in delineating the epidemiology of K. pneumoniae nosocomial infections (6,15). The results provided by PFGE showed that a distinct "in-house" strain (cluster A) was responsible for most colonizations and infections that occurred during hospitalization.…”
Section: Discussionmentioning
confidence: 69%
“…Irrespective of the primary source, it seems that the most significant reservoir of the microorganism is the digestive tract of colonized patients and that transmission occurs mostly via the hands of nursing staff (3,8). During the past decade, strains of K. pneumoniae exhibiting resistance to newer cephalosporins due to the production of extended-spectrum ␤-lactamases (ESBLs) have been frequently implicated in outbreaks in pediatric hospitals and neonatal intensive care units (NICUs) (1,15,16,20). These strains usually exhibit cross-resistance to other antibiotics, such as aminoglycosides.…”
mentioning
confidence: 99%